REPRODUCTIVE PERFORMANCES OF SWAMP BUFFALOES OF ASSAM* - J. SAHARIA5, S. ISLAM1 ; A. K. GOGOI2 N. N. DEKA3 ; J. K.SAIKIA4 (Indian Journal of Animal Production and Management, 2017)
A survey was carried out to study reproductive performances of swamp buffaloes ofthe undivided Kamrup, Nagaon and Darrang district of Assam. A total of 1293 randomlyselected swamp buffaloes were included for the present study. Average age at first calving,gestation period, dry period, service period and intercalving period were found to be 52.28 ±0.81 months, 323.10 ± 0.68, 252.84 ± 1.47, 177.34 ± 0.82 and 465.79 ± 1.67 daysrespectively. Age at first calving was not found to be affected significantly by type of animaland location while season of calving exerted significant effect (P